1998
DOI: 10.1136/jamia.1998.0050177
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Design of Information Systems in Health Care

Abstract: The social environment has to be considered when applying PDIS in health care. Instructions for nondesigners can be used to introduce them to the design objectives, processes, and ideologies on which PDIS is based and to support them when relating clinical and practical design questions to the existing social constraints and norms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 13 publications
0
38
0
2
Order By: Relevance
“…It has become a widely-used approach in a broad range of contexts including both commercially and academically led information system software development projects. [2][3][4][5] It takes numerous forms, but as a broad method it is based on a number of principles including the attempt to build more meaningful and ongoing relationships between those developing software and those who will use it in their day-to-day work. This is achieved through activities that foster discussion, ranging from site visits to workshops to 'games' where software developers and users take on various roles in order to explore the wider meanings within the workplace where a product is to be used.…”
Section: Methodsmentioning
confidence: 99%
“…It has become a widely-used approach in a broad range of contexts including both commercially and academically led information system software development projects. [2][3][4][5] It takes numerous forms, but as a broad method it is based on a number of principles including the attempt to build more meaningful and ongoing relationships between those developing software and those who will use it in their day-to-day work. This is achieved through activities that foster discussion, ranging from site visits to workshops to 'games' where software developers and users take on various roles in order to explore the wider meanings within the workplace where a product is to be used.…”
Section: Methodsmentioning
confidence: 99%
“…Discussion at the workshops suggested that focus groups and follow ups could uncover mismatches between the assumptions of designers and the end-users (Heeks, 2002), such as the stigmas around reminders vs. the opportunity to develop self-esteem though positive messages, as discovered by many of the contributing authors. As GomezMarquez explained, securing user involvement (for example, participatory design processes (Sjöberg and Timpka, 1998)) right from the beginning was critical. By engaging users as designers, face-to-face beside the designer not in front of them during interviews (or worse, kept at a distance via mediated surveys and remote consultations), more optimal directions were discovered, including the opportunity to use cellphone minutes (airtime) as a reward and incentive.…”
Section: Designing For Patients Is Different From Designing For Caregmentioning
confidence: 99%
“…These liaisons and their nature will have a direct impact on the social context for the product implementation and its complete acceptance, later. The product is an artifact that results from the social exchanges in the group and is close to the users [46]. This multiplicity of users usually implies multiple user interfaces and plenty to describe regarding approaches to the design and development of such systems [44].…”
Section: Patient Centered Design For Mental Health Contextsmentioning
confidence: 99%
“…Several approaches gather the vital knowledge needed to prevent rejection of the system, and reduce the information asymmetry usually existent in the implementation process. Few have used a PCD approach in the development of ICT healthcare solutions [3], [46].…”
Section: Patient Centered Design For Mental Health Contextsmentioning
confidence: 99%
See 1 more Smart Citation